2019
DOI: 10.1021/acs.inorgchem.9b00102
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and 1O2 Sensitization Characteristics of a Series of Isomeric Re(bpy)(CO)3Cl Complexes Bearing Pendant BODIPY Chromophores

Abstract: Two new Re(I)bipyridyltricarbonylchloride complexes, Re(BB3)(CO) 3 Cl, and Re(BB4)(CO) 3 Cl, featuring BODIPY groups appended to the 5,5'-, or 6,6'-positions of the bipyridine ligand respectively, have been synthesized as structurally isomeric compliments to a previously reported 4,4'-substituted homologue, Re(BB2)(CO) 3 Cl. X-ray crystal structures of the compounds show that the 4,4'-, 5,5'-and 6,6'-substitution patterns place the BODIPY groups at progressively shorter distances of 9.43 Å, 8.39 Å and 5.56 Å, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 87 publications
4
23
0
Order By: Relevance
“…The large attenuation of ε in the piq series is reproducible over multiple samples, though the origin is not clear. Such an effect has not been previously observed in other 5d metal complexes linked to BODIPY through the meso position 54,6872. The UV and near-visible regions involve several overlapping bands, attributed to a combination of π → π* transitions involving the BODIPY (compare to Fig.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The large attenuation of ε in the piq series is reproducible over multiple samples, though the origin is not clear. Such an effect has not been previously observed in other 5d metal complexes linked to BODIPY through the meso position 54,6872. The UV and near-visible regions involve several overlapping bands, attributed to a combination of π → π* transitions involving the BODIPY (compare to Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Such an effect has not been previously observed in other 5d metal complexes linked to BODIPY through the meso position. 54,[68][69][70][71][72] The UV and nearvisible regions involve several overlapping bands, attributed to a combination of p / p* transitions involving the BODIPY (compare to Fig. S19 †), and the expected bands 73 from the [Ir(C^N) 2 ] + fragment that include C^N-centered p / p* transitions at higher energy and MLCT transitions at lower energy.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“… 22 − 25 As a result, there is great interest in modifying the existing PSs or developing new classes of PSs. Among the latter, rhenium(I) tricarbonyl complexes have been explored in recent years as potential candidates for PDT 26 35 due to their rich photophysical and biochemical properties, including polarized emission, high photostability, large Stokes shifts, triplet states with long lifetimes, and biocompatibility, 36 40 which can also be tuned by varying the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Boron‐dipyrromethene (BODIPY) is considered as a suitable chromophore for complexation to organometallic rhenium core owing to the ease of synthesis and their tunable absorption profile in the visible and NIR region. [ 11,12 ] It was recently reported that two Re(I)‐BODIPY complexes containing ethynyl moieties with enhanced π‐conjugation between chromophore and Re(I) center exhibited absorption in the green region. Efficient intersystem crossing (ISC) was observed in these complexes with triplet state lifetimes of 104 and 127 μs, thereby favoring photosensitized generation of singlet oxygen with quantum yields of Φ Δ = 0.88 and 0.06.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] In another example, a few Re(I)‐bipyridine complexes were prepared, wherein the BODIPY chromophores were attached at varying distances (∼5–10 Å from the metal center), and a relation between 1 O 2 sensitization property and the Re‐BODIPY distal separation was established. [ 12a ] Despite the fact that the photophysical and photosesitization properties of several Re(I)‐BODIPY complexes have been the subject of numerous investigations, their (in vitro/in vivo) biological applications have received limited attention. [ 12d ]…”
Section: Introductionmentioning
confidence: 99%